Pithyriasis lichénoïde: diagnostic pas toujours aussi facile! - Elloudi, Sara (Pan Afr Med J, 2018)
Pityriasis lichenoides is a rare inflammatory dermatosis occurring in young subjects. It evolves into rashes on the trunk and the limbs which regress spontaneously. We here report a particular case of pityriasis lichenoides whose diagnosis was adjusted due to the scar appearance of the lesions. The patient was treated with cyclin and phototherapy, with a favorable outcome.